(untitled) (Вісник: Міжнародні відносини, 2025)
B a c k g r o u n d . Over the past decade, the conflict in Syria has undergone significant evolution. Mass protests have escalated into a civil war, in which regional and global actors have begun to be involved. Russia’s involvement in the conflict has shifted the conflict to a global level. The Syrian crisis has led to global geopolitical transformations that have led to a "big war" in Europe. The article analyzes in detail the causes, objectives, and consequences of Russia’s involvement in the Syrian crisis. M e t h o d s . The study is based on a combination of three scientific approaches: political realism, constructivism, and a systemic approach. Such a synthesis allows us to see how the participation of the Russian Federation in the Syrian conflict has affected the change in the global balance of power, to clarify the real objectives of the Russian military operation in Syria, and to establish a connection between the Syrian crisis and the Russian Federation’s war against Ukraine. R e s u l t s . The article analyzes the evolution of Russia’s foreign policy in the 21st century, establishes the reasons and motives for changing the Kremlin’s foreign policy course, identifies the real objectives of Russia’s intervention in Syria, examines geopolitical transformations during the Syrian crisis, and proves that the Russian Federation’s large-scale aggression against Ukraine is a direct consequence of Moscow’s impunity in Syria. C o n c l u s i o n s . The foreign policy of the Russian Federation in the 21st century has undergone a significant transformation: from partnership relations with the United States to a complete transition to the "Primakov doctrine". Within the framework of this doctrine, Russia carried out aggression against Ukraine in 2014 and military intervention in Syria in 2015. The main task of the Russian Federation in Syria was to "rehearse" a full-scale war in Ukraine. The weakness of the international community, primarily the United States, in holding the Syrian regime and its Kremlin patrons accountable for the war crimes they committed in Syria prompted Moscow to further aggression.